Child Survival and Policy Options in Kenya: Evidence from Demographic and Health Surveys - Kabubo-Mariara, Jane; Karienyeh, Margaret M.; Kabubo, Francis M. (Journal of Reviews on Global Economics, 2012)
Abstract: This paper investigates child survival in Kenya. We use survival analysis to explain childhood mortality and further simulate the impact of key policy variables on millennium development goals targets for mortality. The results show that favorable child and maternal characteristics, and household assets are associated with higher probability of survival at time t. The results further show that health care services are crucial for child survival. Policy simulations suggest that maternal education and use of modern contraception methods are key policy issues for child survival. The simulations further suggest that it is unlikely that the millennium development goals targets will be achieved.